Lignans isolated from the ethyl acetate extract of Knema pachycarpa fruit - Tung, To Hai; Hue, Cao Thi; Giap, Tran Huu; Thoa, Ha Thi; Dung, Nguyen Anh; Minh Hang, Nguyen Thi; Hung, Nguyen Van; Thanh, Le Nguyen (Vietnam Journal of Chemistry, 2017)
Knema is a genus of tropical evergreen trees of the family Myristicaceae found in South East Asian countries such as Vietnam, Thailand, and Malaysia. In this paper, four lignans, (+)-pinoresinol (1),(+) epi-pinoresinol (2), piperitol (3), and pluviatilol (4), were isolated from the ethyl acetate extract of the fruit of Knema pachycarpa, an indigenus tree in Vietnam. The chemical structures were determined by spectroscopic data and comparison with the reported literature. These compounds were isolated from Knema genus for the first time. Keywords. Knema pachycarpa de Wilde, (+)-Pinoresinol, (+)-Epi-pinoresinol, Piperitol, Pluviatilol.